2016
DOI: 10.1074/mcp.m116.060723
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Phagocytic Immune Cells in Anopheles gambiae Reveals Integral Roles for Hemocytes in Mosquito Innate Immunity

Abstract: The innate immune response is highly conserved across all eukaryotes and has been studied in great detail in several model organisms. Hemocytes, the primary immune cell population in mosquitoes, are important components of the mosquito innate immune response, yet critical aspects of their biology have remained uncharacterized. Using a novel method of enrichment, we isolated phagocytic granulocytes and quantified their proteomes by mass spectrometry. The data demonstrate that phagocytosis, blood-feeding, and Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(113 citation statements)
references
References 66 publications
(120 reference statements)
9
102
2
Order By: Relevance
“…Smith et al using magnetic bead isolation at 28°C only (Smith et al, 2016). Our analyses revealed 340 that similarities were the strongest when profiles were compared across all samples -PPO6 high , 341 PPO6 low , phagocytes and all cells, i.e.…”
Section: Ppo6 High and Ppo6 Low Cells Represent Transcriptionally Dismentioning
confidence: 72%
“…Smith et al using magnetic bead isolation at 28°C only (Smith et al, 2016). Our analyses revealed 340 that similarities were the strongest when profiles were compared across all samples -PPO6 high , 341 PPO6 low , phagocytes and all cells, i.e.…”
Section: Ppo6 High and Ppo6 Low Cells Represent Transcriptionally Dismentioning
confidence: 72%
“…Transcriptomic and proteomic studies comparing gene and protein expression between hemocytes and carcass in An. gambiae identified some genes enriched in immune cells (Baton, Robertson et al 2009, Lombardo, Ghani et al 2013, Smith, King et al 2016, Kwon and Smith 2019. Promoters of these genes could therefore constitute other good candidates to drive expression in mosquito hemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae adult females, bacterial or parasite challenges also trigger hemocyte differentiation (King and Hillyer 2012, King and Hillyer 2013, Ramirez, Garver et al 2014 and this is associated with differences in their gene and protein expression (Baton, Robertson et al 2009, Pinto, Lombardo et al 2009, Smith, King et al 2016. Moreover, hemocytes are involved in phagocytosis (Moita, Wang-Sattler et al 2005, King and Hillyer 2012, King and Hillyer 2013, Lombardo, Ghani et al 2013) and in immune responses against malaria parasites (Pinto, Lombardo et al 2009, Ramirez, Garver et al 2014, Smith, Barillas-Mury et al 2015, Lombardo and Christophides 2016, Smith, King et al 2016. Immune cell differentiation has also been implicated in innate immune memory (Ramirez, Garver et al 2014, Ramirez, de Almeida Oliveira et al 2015, Barletta, Trisnadi et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Following liposome treatments, hemolymph was perfused from individual mosquitoes (n=15) at naïve or 24 h P. berghei -infected mosquitoes using incomplete buffer (anticoagulant solution without fetal bovine serum) containing a protease inhibitor cocktail (Sigma) (10). Hemolymph protein concentrations were measured using Quick Start ™ Bradford Dye reagent (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that Anopheles gambiae hemocytes respond to blood-feeding (710), as well as bacterial and malaria parasite challenge (3, 11), eliciting changes in their cellular profiles at the transcriptional (12, 13) and proteome levels (10). This has led to the identification of several mosquito hemocyte components with integral roles in phagocytosis (14, 15) and anti- Plasmodium immunity (10, 12, 16). In addition, hemocyte differentiation in response to malaria parasite challenge has been described as an integral requirement of mosquito immune priming (1719) and the “late-phase” immune responses targeting Plasmodium oocyst survival (2022).…”
Section: Introductionmentioning
confidence: 99%